Maternal and paternal harsh parenting and anxiety symptoms in Chinese adolescents: examining a multiple mediation model - Xiujuan Yang; Ling Lin; Wen Feng; Pei Liu; Nana Liang; Zhenpeng Xue; Yuejiao Ma; Yuan Shen; Wenwen Yu; Jianping Lu; Jianbo Liu (BMC, 2024)
Abstract Background Harsh parenting has been recognized as a risk factor for adolescent anxiety; however, the underlying mechanisms of this relationship remain unclear, and it is unknown whether this relationship is influenced by different parental roles and living arrangements. This study aimed to investigate the mediating mechanisms between harsh parenting and adolescent anxiety symptoms using a multiple mediation model and to further compare specific roles of harsh parenting and distinguish between the living arrangements. Methods A total of 3505 adolescents completed this survey, and 3295 adolescents (54.7% girls, Mage = 14.97 years) were included in the study. Participants completed self-assessments measuring harsh parenting, self-efficacy, school connectedness, Internet addiction, sleep problems, and anxiety. They were categorized into three groups based on living arrangements: living with both parents, only with the mother, or only with the father. Results Correlational analyses revealed that both maternal and paternal harsh parenting were associated with increased anxiety symptoms. Structural equation modeling (SEM) mediation analyses and multigroup analyses showed that the independent mediating effects of school connectedness, Internet addiction, and sleep problems, as well as the sequential mediating pathways involving self-efficacy → school connectedness, self-efficacy → Internet addiction, and self-efficacy → sleep problems, vary across the adolescents' living arrangements in the association between maternal and paternal harsh parenting and adolescent anxiety symptoms. Conclusions This study elucidated the mechanisms linking harsh parenting to adolescent anxiety symptoms and validated the effects of different parental roles and living arrangements. The findings provide important insights for developing targeted interventions to address anxiety symptoms in adolescents exposed to harsh parenting.